The Influence of Turkish Ottoman Islamic Civil Law in 19th Century in the State of Johor, Malaysia - Abd Jalil, Borham (Center for Promoting Ideas (CPI) USA, 2013)
Sultan Abu Bakar of Johor was responsible for foreign policy of his country, had a different series of visits and the establishment of diplomatic relations with countries in Europe and the Middle East. Looking at this policy was not surprising, that Johor was the first Malaysia state has its own written constitution in 1895. Position as a state which was in the process of implementing Islamic law can be seen when Johor have good relationship with the Turkish Ottoman Government. The biggest Turkish influence in the administration of Islamic law in the state of Johor was the implementation of Islamic civil law named Majalah Ahkam Johor. This Majalah has been taken from Majallah al-Ahkam al-`Adliyyah of Ottoman Government implemented in Turkey in the 19th century AD and its influence spread throughout a colony of Turkey at that time. This shows the Johor Government's relationship with the Government of Ottoman have gone so close, particularly when under the reign of Sultan Abu Bakar and generally before the existence of the Malacca Islamic government. Marital relations, trade, culture, arts, law and others to convince us that strong relationship between the two countries have gone a long time.